Self-advocacy positive perceptions and stage experiences in patients who had a stroke: a qualitative study in China - Shanshan Wang; Zhen-Xiang Zhang; Yong-Xia Mei; Chunhui Zhang; Bei-lei Lin; Hu Jiang; Xiaoxuan Wang; Zhixin Zhao (BMJ Open)
Objectives This study explored the perceptions and experiences of self-advocacy among patients who had a stroke in China.Design A descriptive phenomenological qualitative study was performed. Colaizzi’s seven-step method was used to analyse the data.Setting Two hospitals in Zhengzhou and Luoyang City, Henan Province, China.Participants 19 patients who had a stroke were recruited and interviewed face-to-face between October 2023 and February 2024.Results The findings revealed two categories: positive perceptions and stage experiences. Three themes of positive perceptions were extracted: ‘accept the facts of illness while maintaining inner integrity’ with three subthemes (disease cognition, firm faith and positive attitude); ‘clarify one’s own needs and strive for them’ with four subthemes (self-care knowledge, effective communication, independent decision-making and power from relation); ‘enhancing subjective initiative and maintaining healthy behaviours’ with three subthemes (active participant in disease management, increased treatment compliance and increased initiative in rehabilitation exercises). Three stage experiences themes were motivation, response and stabilisation stage.Conclusions In this study, patients who had a stroke showed more positive perceptions of self-advocacy. Self-advocacy is a dynamic and progressive process of accepting their disease and actively participating in disease treatment. In addition, patients’ health behaviours are improved and maintained when they engage in self-advocacy.